Effective short term treatment of Paget's disease with oral etidronate. - Preston, C; Yates, A; Beneton, M; Russell, R; Gray, R; Smith, R; Kanis, J (1986)
Twelve patients with Paget's disease of bone were treated with high doses of disodium etidronate for one month and compared with patients given treatments for longer periods. The effects of treatment for one month with etidronate 20 mg/kg daily were indistinguishable from six months' continuous treatment with the same dose but significantly better than treatment with 5 mg/kg daily in suppressing biochemical indices of disease activity. Treatment for one month was associated with transient osteomalacia but sustained suppression of bone resorption. Short term treatments with high doses of disodium etidronate may maximise suppression of disease activity but decrease exposure to unwanted effects.